EFFICACY OF TRIAMCINOLONE ACETONIDE INTRALESIONAL INJECTION IN THE TREATMENT OF NAIL PSORIASIS (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate efficacy of triamcinolone acetonide intralesional injection in the treatment of nail psoriasis.Methods: Non-controlled interventional study on 79 nails of 11 psoriasis patients at National Hospital of Dermatology and Venereology from August 2020 to August 2021.Results: Amount of pitting lesion was 67 nails at baseline, which statistically significant decrease at the 2nd month with 57 nails (p=0.016) and at the 4th month with 54 nails (p=0.014), however there was no difference between the 2nd and 4th month (p=0.192); while, there was no difference in transverse ridging, crumbling, leukonychia at the 2nd and 4th months. Amount of subungual hyperkeratosis was 61 nails at baseline, statistically significant decrease at the 2nd month with 52 nails (p=0.031) and the 4th month with 50 nails (p=0.019), however there is no difference between the 2nd and 4th month (p=0.167); there was no difference in oil drops, onycholysis, and splinter hemorrhage at 2nd and 4th months. Nail Psoriasis Severity Index (NAPSI) decreased statistically at 2nd months with an average decrease of 5.1±6.5 (p=0.000) and continued to decrease at 4th months with a decrease compared to the 2nd month of 1.5±2.7 (p=0,000). Nijmegen nail psoriasis Activity Index Tool (N-NAIL) decreased statistically significantly at 2nd months with an average decrease of 8.4±8.3 (p=0.000) and continued to decrease at 4th month with a decrease compared to the 2nd month is 5.3±6.4 (p=0.000). Side effects are mainly local, including skin atrophy, vasodilation; 33 percent of female patients had menstrual disorder. None of patients had flare-ups.Conclusion: Triamcinolone acetonide intralesional injection is a fairly safe method, helping to improve nail pitting and subungual hyperkeratosis at 2nd months and 4th months, but no difference between 2nd months and 4th months; other lesions do not change. This therapy also reduced NAPSI and N-NAIL scores at both 2nd and 4th months.
Keywords: Nail matrix lesions, nail bed lesions, NAPSI, N-NAIL.